IMPLEMENTATION OF ZAKAT FUND EMPOWERMENT MODEL, INFAQ, SHADAQAH IN BADAN AMIL ZAKAT NASIONAL (BAZNAS) MADIUN CITY - Mohammad Dendi Abdul Nasir (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
Human needs are ever-increasing and developing. Therefore economic activity is inevitable and Islamic philanthropy has a crucial role in this development. Because some problems related to economic inequality and underdevelopment cannot be faced personally, it requires togetherness and cares especially economic interactions between muzak and mustahiq. National Alms Agency of Madiun city, as a pioneer related to such interaction, has a vital role in economic empowerment, especially for Madiun City. Because it becomes crucial to know the application of the zakat, infaq, and sadaqah fund utilization models because it can be one of the successes in minimizing economic inequality and underdevelopment, this research utilizes a descriptive method qualitative approach. There are five research subjects. The type of research data uses primary and secondary data type. Methods used in data collection include interviews, observation, document, and observation. This study shows that the activities of zakat, infaq, and sadaqah fund utilization models at the National Alms Agency of Madiun City took the form of consumptive distribution and productive distribution utilization. The utilization of traditional consumptive distribution in the form of calamity and disaster aid, and the creative utilization of consumptive distribution in the form of health assistance and educational assistance or scholarships. Whereas the utilization of productive distribution uses the surplus zakat budged model, where the collection of zakat funds is then distributed in part, and the rest is used for productive projects—utilization of productive distribution in the form of work tools business capital under BAZNAS Madiun City guidance.